2020
DOI: 10.7759/cureus.11267
|View full text |Cite
|
Sign up to set email alerts
|

Single-Isocenter Volumetric Modulated Arc Therapy (VMAT) Radiosurgery for Multiple Brain Metastases: Potential Loss of Target(s) Coverage Due to Isocenter Misalignment

Abstract: Purpose A single-isocenter volumetric modulated arc therapy (VMAT) treatment to multiple brain metastatic patients is an efficient stereotactic radiosurgery (SRS) option. However, the current clinical practice of single-isocenter SRS does not account for patient setup uncertainty, which degrades treatment delivery accuracy. This study quantifies the loss of target coverage and potential collateral dose to normal tissue due to clinically observable isocenter misalignment. Methods and mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…On the other hand, our TrueBeam Linac is capable of applying both rotational and translational couch corrections and may better align multiple lesions on a single daily CBCT scan and minimize the patient set up errors in the treatment of LNs SBRT. A few recent studies have shown loss of target coverage due to rotational set up errors in a single‐isocenter/multilesions setting 46–48 . However, the exact magnitude of dosimetric discrepancy in using six‐degrees‐of‐freedom (6DOF) couch corrections for treating multiple LNs SBRT treatment on Halcyon is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our TrueBeam Linac is capable of applying both rotational and translational couch corrections and may better align multiple lesions on a single daily CBCT scan and minimize the patient set up errors in the treatment of LNs SBRT. A few recent studies have shown loss of target coverage due to rotational set up errors in a single‐isocenter/multilesions setting 46–48 . However, the exact magnitude of dosimetric discrepancy in using six‐degrees‐of‐freedom (6DOF) couch corrections for treating multiple LNs SBRT treatment on Halcyon is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…Treating m‐bm with a single‐isocenter plan comes with many challenges, including dosimetric disparities, due to patient positioning errors 14–20 . This presents concerns in terms of local tumor control and unexpected dosing to the normal brain and other adjacent critical structures in the brain as described above.…”
Section: Discussionmentioning
confidence: 99%
“…Treating m‐bm with a single‐isocenter plan comes with many challenges, including dosimetric disparities, due to patient positioning errors. 14 , 15 , 16 , 17 , 18 , 19 , 20 This presents concerns in terms of local tumor control and unexpected dosing to the normal brain and other adjacent critical structures in the brain as described above. The QUANTEC guidelines for normal brain tissue cite a study relating V12Gy to radiation‐induced necrosis, where the risk of NTCP increases from 23% for V12Gy between 0 and 5 cc and 54% for V12Gy at 10 to 15 cc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations